HEALTH COUNSELING ON HOW TO OVERCOME ANXIETY WITH PROGRESSIVE MUSCLE RELAXATION IN THE ELDERLY IN TUKMUDAL VILLAGE, SUMBER DISTRICT - Riza Arisanty Latifah; Leya Indah Permatasari; Aningsih (Jurnal Abdisci, 2024)
Anxiety is a psychological disorder characterized by excessive and persistent feelings of fear and worry. Anxiety often occurs in the elderly, which makes the elderly feel anxious and excessively restless, so it interferes with daily activities. Symptoms of anxiety are restlessness, trembling, headaches, and the heart rate becomes faster than usual. The purpose of this health counseling is to increase public knowledge on how to overcome anxiety. The implementation method starts with a survey and then conducts counseling with education, role play, and evaluation. The results achieved in this counseling are that the elderly who participate in health education activities about overcoming anxiety in the elderly can understand how to overcome anxiety in the elderly in Tukmudal Village and increase public knowledge about anxiety. The conclusion is that this counseling has been carried out and based on the results of the evaluation of the implementation during the activity, it is known that there has been an increase in the knowledge of the elderly about anxiety and how to overcome anxiety in Tukmudal Village, Sumber District, Cirebon Regency.